(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Land ownership and land mastery are two things that build rural structures in the community. In the peasant community, the Agrarian structure becomes the determinant of other aspects of life, such as agricultural production rate, income level as well as economic and other social factors. The importance of Agrarian structure in the peasant community makes researchers conduct a study aimed at analysing the typology of the Agrarian structure of transmigrant farmers in South Konawe Province of Southeast Sulawesi through a combination of ownership aspects and mastery aspects. This research used qualitative methods by taking one case, namely in the Transmigration Settlement Unit (UPT) Arongo in Southeast Sulawesi Province. The results showed that through the combination of aspects of land ownership and land mastery as a form of Agrarian structure, there are three typologies of Agrarian structure form in the UPT. Arongo, owning and mastering agricultural land, owning but not mastering land and not owning but mastering land. To achieve Agrarian transformation, the ideal typology of Agrarian structures for peasant communities is in the form of Agrarian structures in which people own land while mastering it so that land management is optimal.